Nutritional status and interventions for patients with cancer – A systematic review. Issue 1 (January 2021) - Hamaker, Marije E.; Oosterlaan, Fleur; van Huis, Lieke H.; Thielen, Noortje; Vondeling, Ariel; van den Bos, Frederiek
Abstract: Background: Malnourishment is commonly seen in ageing, cancer and many chronic conditions, and is associated with poorer prognosis. Aim: We set out to collect all currently available evidence on the association between nutritional status assessed with a validated screening tool and prognosis or course of treatment in older patients with cancer, and on the benefit of nutritional interventions in improving these outcomes. Methods: A systematic search in MEDLINE and EMBASE. Results: We included 71 studies on the association between nutritional status and outcome in (older) patients with cancer and 17 studies on the benefit of nutritional interventions in improving outcomes in this patient population. There is a significant association between nutritional status and increased intermediate- and long-term mortality (hazard ratio 1.87 (95% confidence interval 1.62–2.17). Those with poorer nutritional status were less likely to complete oncologic treatment according to plan and had higher health care consumption. Benefit of dietary interventions was limited although dietary counselling may lead to improved quality of life while nutritional support may lead to a decrease in post-operative complication rates. Conclusion: Nutritional status is associated with poorer survival, decreased treatment completion and higher health care consumption and nutritional interventions are only able to negate these negatives outcome to a very limited degree.